Analysis of the Need for Reduction in Force of Professional Personnel - Grays Harbor Coll., Aberdeen, WA.; Grays Harbor Coll., Aberdeen, WA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Results of a self-study made of the institutional planning and management of Grays Harbor College are provided. The study utilized the Systems Evaluation Applied to Renewal and Change (SEARCH) program. An analysis of the general application of the funding formula, as used in the community college system in Washington, discusses instruction funding, libraries funding, plant maintenance and operations funding, student services funding, and Administration funding. The major staffing difficulty, relative to available funds, was in the area of teaching personnel; thus, an analysis was made of the statewide average student/faculty ratio as compared with the student/faculty ratio by instructional division of the college. The results of the SEARCH study are presented as to administrative conclusions and decisions, major criteria to be utilized, and expected effect on the curriculum (Life Science Division, Business Administration Division, English-Speech Division, Health and Physical Education Division, Social Science Division, Science and Mathematics Division, Humanities Division, Vocational Division, and Administration Division). Appendixes present: A. Financial Analysis for 1973-1974; B. chart of State General Fund--Dollars per FTE; C. Non-teaching Professional Personnel MIS-6, Community College System; D. Community College Librarians; E. Community College Counselors; F. System Ratios of Classified Employees to FTE; G. and H. copies of correspondence; I. Comparison of Over-all GHC Divisional Faculty/Student Ratios to Appropriate Clusters of State Over-all Faculty/Student Ratios, Tenure Regulations, and Academic Employee Reduction Procedure. (DB)
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Administration; College Faculty; Community Colleges; Comparative Analysis; Financial Problems; Institutional Research; Job Layoff; Postsecondary Education; Research Reports; Student Teacher Ratio; Systems Approach; Tables (Data); Teacher Dismissal; Grays Harbor College WA; Washington; Reports, Research